PENGABDIAN KEPADA MASYARAKAT: PROGRAM KEAKSARAAN BAGI WARGA BINAAN RUTAN KELAS IIB MAJENE - Hertanti, Alfiramita; Aprisal, Aprisal; Nurfiani, Nurfiani (LPPM Universitas Flores, 2024)
One of the problems faced by society is the still high rate of illiteracy. Therefore, it is necessary to take steps to eradicate illiteracy. SPNF-SKB Kab. Majene, in collaboration with Rutan Kelas IIB Majene, is implementing a literacy program to improve the reading, writing and counting skills of the inmates of the Rutan Kelas IIB Majene. This program was attended by 12 inmates for approximately 6 months and was carried out once every week. This program consists of four main stages, namely: observation of service locations, preparation of service equipment, implementation of service, and evaluation of service activities. As a result of service activities through the literacy program, there was a significant increase in the reading, writing and counting abilities of the inmates. 8 people were deemed no longer necessary to take part in a literacy program and were recommended to take part in another program at a higher level.